The common good: the inclusion of non‐Catholic students in Catholic schools - Donlevy, J. Kent (2008)
This paper offers that liberal and communitarian concepts of the common good are exemplified in the Catholic school’s policy of the inclusion of non‐Catholic students. In particular, the liberal concepts of personal autonomy, individual rights and freedoms, and the principles of fairness, justice, equality and respect for diversity - as democratic ideals - are evidenced in inclusion. Moreover, the communitarian concepts of the situated self, community values and mutual responsibility for Catholic and non‐Catholic students and Catholic teachers are nurtured with inclusion. The conclusion reached by the paper is that Catholic schools, through the practice of inclusion, exemplify the common good in both the liberal and communitarian traditions and therefore serve as an exemplar for the wider democratic society.
Keywords: Catholic Schools; Common Good; non‐Catholic students